Persepsi Petani terhadap Implementasi Teknologi Informasi dan Komunikasi dalam Penyuluhan Pertanian - Sirajuddin, Zulham; Liskawati Kamba, Pepi (Jurnal Penyuluhan, 2021)
In the era of Industry 4.0, the use of Information and Communication Technology (ICT) is vital in agricultural extension. However, there are still variations in the use and adoption of ICTs at the  farmer levels as not every region can optimize the use of ICT in agricultural extension. This study aims to identify the diversity of access to ICT by farmers, and identify farmers' perceptions of the use of ICT. This study used a survey method with quantitative descriptive data analysis, distributed to 73 sample respondents. The questionnaire was compiled using the Technology Acceptance Model (TAM) theory lens, using two aspects in analyzing technology acceptance: perceived usefulness and perceived ease of use. The results showed that the use of smartphones by farmers was high with access ownership above 60%. ICT is well accepted by respondents compared to conventional media. There is a significant relationship between the education level of farmers and perceived ease of use, with a correlation coefficient of .322. It can be concluded that smartphones have considerable potential to be used in agricultural extension, and there is a need of strategy to improve the ease of use of smartphones for farmers with low education level.